The Law Principles for Village-Owned Enterprises (BUMDes) Managementin Indonesia to Improve the Village's Economy - Sri Winarsi; Agus Widyantoro; Oemar Moechthar (Fakultas Hukum, Universitas Warmadewa, 2018)
Toward the increase in village revenue sources, a post of published Law No. 6/2014 concerning Village, it is confirmed that the village can establish village-owned enterprises (BUMDes) based on family spirit and cooperativeness. Besides, BUMDes can run a business in the field of economic and/or public service in accordance with the provisions of the legislation. BUMDes is established by the village government to utilize all potential economic, institutional, natural, and human resources in order to improve the welfare of the villagers. In fact, implementation of the BUMDes management in some areas is not fully optimized, in many cases the problem is corruption. Therefore, we need a good management or governance practices to improving the livelihoods of the village. The study used statute approach, conceptual approach, and case approach. The conclusions of this study are directed to apply the concepts of strengthening national laws relating to the management of BUMDes in order to strengthen the village's economy in Indonesia and to achieve empowerment of rural community and reduce corruptionthat often occurs and harm the economy of the village.